Does therapeutic temperature management after cardiac arrest increase the risk of bleeding? - Inoue, Madoka; McKenzie, N.; Williams, Teresa (Elsevier Ireland Ltd, 2015)
This report critiques a systematic review and meta-analysis that examined the relationship of bleeding with TTM - "Therapeutic temperature management after cardiac arrest and the risk of bleeding: Systematic review and meta-analysis for the effect of therapeutic temperature management after cardiac arrest".